2010
DOI: 10.1021/ml9000276
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Narlaprevir (SCH 900518): A Potent, Second Generation HCV NS3 Serine Protease Inhibitor

Abstract: Boceprevir (SCH 503034), 1, a novel HCV NS3 serine protease inhibitor discovered in our laboratories, is currently undergoing phase III clinical trials. Detailed investigations toward a second generation protease inhibitor culminated in the discovery of narlaprevir (SCH 900518), 37, with improved potency (∼10-fold over 1), pharmacokinetic profile and physicochemical characteristics, currently in phase II human trials. Exploration of synthetic sequence for preparation of 37 resulted in a route that required no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 22 publications
(39 reference statements)
0
40
0
3
Order By: Relevance
“…Of note, replicon cells resistant to SCH 900518 remained sensitive to interferon alfa-2b. X-ray structural analysis (1) showed that the A156 side chain is in van der Waals contact with the P2 and P4 side chains of SCH 900518. Mutation of A156 to bulkier residues (Ser/Thr/Val) causes stereo hindrance in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, replicon cells resistant to SCH 900518 remained sensitive to interferon alfa-2b. X-ray structural analysis (1) showed that the A156 side chain is in van der Waals contact with the P2 and P4 side chains of SCH 900518. Mutation of A156 to bulkier residues (Ser/Thr/Val) causes stereo hindrance in the region.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of SCH 900518 complexed with the NS3-NS4A protease was solved in-house (1). To illustrate the key resistance-conferring loci, the structure of SCH 900518 is presented as a stick model, and the side chains of residues are shown by using CPK models on the Connolly surface of the NS3 protease.…”
mentioning
confidence: 99%
“…2735 However, despite potent activity against wild-type GT-1, PIs suffer from a low genetic barrier to resistance. 36 We have previously described the molecular basis for resistance to many of these inhibitors in terms of the substrate envelope and macrocyclization.…”
Section: Introductionmentioning
confidence: 99%
“…Developed as all‐oral once daily dosing, these would need to be co‐administered with other DAAs in order to overcome resistance barriers. Their SARs as collated during the process of discovery have also been made public . Across the board, structural modification of P 2 residues in particular produced remarkable improvement in potency as well as safety.…”
Section: Inhibitors Of Proteases From Microbial Pathogensmentioning
confidence: 99%